Analysis of Employee Empowerment and Career Development on Employee Job Satisfaction at the Public Works, Bina Marga, and Spatial Planning Department of Palembang City - Badriyah, Nur Farihah; Lazuarni, Shafiera; Kurniawan, Mohammad (Jurnal Ilmiah Sumber Daya Manusia, 2025)
With the rapid advancement of technology, government institutions are required to enhance performance and efficiency in public services. This study aims to analyze the influence of employee empowerment and career development on job satisfaction among employees at the Public Works, Highways, and Spatial Planning Office of Palembang City. The study employed purposive sampling with a total of 133 respondents, consisting of employees who have worked at the institution for at least one year. Data analysis was conducted using SPSS (Statistical Program and Services Solutions) version 26. The results indicate that both employee empowerment and career development have a positive and significant effect on job satisfaction. The managerial implication of these findings suggests that the organization’s management should prioritize empowerment and career development programs as strategic efforts to improve employee satisfaction, which in turn may enhance overall organizational performance. This research also contributes to the United Nations Sustainable Development Goals (UN SDGs) number 9, which is related to infrastructure and innovation as drivers of economic growth and development.